Zawartość formy ogólnej i łatwo przyswajalnej miedzi w pyłach drogowych w Zielonej Górze = Total and soluble copper content in street dust in Zielona Góra - Walczak, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents results of research work on the content of copper (total and soluble) in street dusts from the area of Zielona Góra, Poland. Street dust was defined as a material from arterial roads in the city).Concentrations of copper in street dust are higher than in soils surrounding streets in Zielona Góra.
Keywords: miedź; pyły drogowe; copper; street dust